The Implementation of Ethnoscience Integrated Problem-Based Learning: A Quantitative Research in Junior High School Science Education of Cirebon Terasi Production to Enhance Critical Thinking Skills - Norma Bastian; Widodo Setyo Wibowo; Dwi Purbowati (Universitas Muhammadiyah Cirebon, 2025)
Critical thinking skills constitute fundamental competencies that students must develop to meet the demands of twenty-first-century education. However, science instruction in Indonesian junior high schools frequently lacks integration of local cultural contexts, thereby impeding students' capacity to connect scientific concepts to authentic real-world situations. This study aimed to examine the effect of Problem-Based Learning (PBL) integrated with the ethnoscience of Cirebon terasi (fermented shrimp paste) production on the critical thinking skills of junior high school science students. A quasi-experimental design with a pretest-posttest control group arrangement was employed. Participants comprised 68 seventh-grade students from SMPN 1 Cirebon, randomly assigned to an experimental group (n = 34) receiving PBL integrated with ethnoscience instruction and a control group (n = 34) receiving conventional instruction. Data were gathered using a validated critical thinking skills instrument based on Facione's six-dimensional framework, encompassing interpretation, analysis, evaluation, inference, explanation, and self-regulation. The instrument demonstrated high content validity (CVR = 0.87) and reliability (Cronbach's α = 0.89). Results indicated a statistically significant difference in critical thinking skills between the experimental and control groups (t(66) = 11.42, p < 0.001), with normalized gain (N-gain) values of 0.72 (high category) and 0.35 (medium category), respectively, and a very large effect size (Cohen's d = 2.64). The greatest improvement was observed in the evaluation dimension (N-gain = 0.78). Furthermore, 87.6% of students expressed positive responses toward the ethnoscience-integrated PBL approach. These findings confirm that contextualizing science learning within the local wisdom of Cirebon terasi production through PBL significantly enhances critical thinking skills, thereby offering a culturally responsive and pedagogically robust model for science education in Indonesian junior high schools.